2021
DOI: 10.3390/pathogens10050548
|View full text |Cite
|
Sign up to set email alerts
|

Bioverm® in the Control of Nematodes in Beef Cattle Raised in the Central-West Region of Brazil

Abstract: Cooperia, Haemonchus and Oesophagostomum are the genera of gastrointestinal parasitic nematodes most prevalent in cattle and constitute a serious problem in cattle breeding due to the impact they have on meat and milk production and the high costs of control measures. The objective of the present work was to evaluate the efficiency of Bioverm® (Duddingtonia flagrans) in the control of gastrointestinal parasitism of young cattle raised in the field, in the Central-West region of Brazil. The experiment was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The statistically significant difference in the penultimate weighing of this study, in which greater weight gain was observed in the treated group compared to the control group, may indicate some action of the fungus. Oliveira et al [18] also recorded an increase in weight gain in animals that received the fungus for six months compared to the control group, however, in the case of a larvicidal and non-ovicidal fungus.…”
Section: Resultsmentioning
confidence: 94%
“…The statistically significant difference in the penultimate weighing of this study, in which greater weight gain was observed in the treated group compared to the control group, may indicate some action of the fungus. Oliveira et al [18] also recorded an increase in weight gain in animals that received the fungus for six months compared to the control group, however, in the case of a larvicidal and non-ovicidal fungus.…”
Section: Resultsmentioning
confidence: 94%
“…Both larvicidal and ovicidal fungi have been used in several in vitro and in vivo experiments, being unanimously considered an accurate and sustainable tool for the control of GI parasites, resulting in a reduction in the number of eggs per gram of feces (EPG) of 60-97% in field trials with grazing animals [28,[31][32][33][34][35]. The lack of adverse effects of D. flagrans on soil nematodes [36], as well as the innocuousness of M. circinelloides and D. flagrans on several animal species [35,37] should also be underlined.…”
Section: Biocontrol Of Gi Parasites Using Predatory Fungimentioning
confidence: 99%
“…In the last five years, commercial formulations containing D. flagrans started became commercially available. In Brazil (Bioverm ® -AC001, GhenVet Saúde Animal, Paulínia, Brazil), Australia, and New Zealand (BioWorma ® -NCIMB 30336, BioWorma, Sydney, Australia), these products are already used, with administration in animal feed [8,[11][12][13][14].…”
Section: Brief History Of Helminthophagous Fungimentioning
confidence: 99%
“…It has been proven that after oral administration of D. flagrans (AC001-Bioverm ® , GhenVet Saúde Animal, Paulínia, Brazil), at a dosage of 1 g/10 kg of body weight (10 5 chlamydospores/g), there was fungal survival after passage through the gastrointestinal tract of sheep and cattle, with efficient larval predation in vitro [8,14]. Under field conditions, the daily administration of Bioverm ® for six months demonstrated a significant parasitic reduction in cattle and horses in Brazil [12,13]. The use of biological control by helminthophagous fungi provides an option to reduce the rates of contamination by larvae and, consequently, less reinfection for the animals, enabling them to develop natural immunity against the helminths.…”
Section: Advances In the Control Of Gastrointestinal Nematodes In Pasture Animalsmentioning
confidence: 99%